Analisis Hasil Uji Pembangkit Listrik Hybrid Turbin Angin 1kWh Dan Panel Surya 100 WP - Hastuti Aziz; Pawenary IPM; Meyhart Bangkit Sitorus (Sekolah Tinggi Teknik - PLN, 2019)
Electrification ratios in some isolated regions and scattered islands in Indonesia are still very low. Until now, most of the electricity needs in Indonesia are still supplied by Diesel Power Plants (PLTD) that use fossil energy as their main fuel. There fore, the use of renewable energy is needed as one of the steps in meeting electricity needs. In this study will be studied about Hybrid Power Generators that utilize wind energy or wind using low speed turbine hybrid by utilizing solar energy using solar panels as an alternative to meet the needs of electrical energy in isolated areas and islands outermost in Indonesia. Testing is done on a small scale. The results obtained from the efficiency of the hybrid system are still less than 30%, namely 11.2% which shows poor performance. The total electricity produced per day is 2.7 kWh.